Impact of Tigecycline's MIC in the Outcome of Critically Ill Patients with Carbapenemase-Producing Klebsiella pneumoniae Bacteraemia Treated with Tigecycline Monotherapy-Validation of 2019's EUCAST Proposed Breakpoint Changes - Matthaios Papadimitriou-Olivgeris; Christina Bartzavali; Alexandra Nikolopoulou; Fevronia Kolonitsiou; Virginia Mplani; Iris Spiliopoulou; Myrto Christofidou; Fotini Fligou; Markos Marangos (MDPI AG, 2020)
Background: Tigecycline is a therapeutic option for carbapenemase-producing Klebsiella pneumoniae (CP-Kp). Our aim was to evaluate the impact of the tigecycline's minimum inhibitory concentration (MIC) in the outcome of patients with CP-Kp bacteraemia treated with tigecycline monotherapy. Methods: Patients with monomicrobial bacteraemia due to CP-Kp that received appropriate targeted monotherapy or no appropriate treatment were included. Primary outcome was 30-day mortality. MICs of meropenem, tigecycline, and ceftazidime/avibactam were determined by Etest, whereas for colistin, the broth microdilution method was applied. PCR for blaKPC, blaVIM, blaNDM, and blaOXA genes was applied. Results: Among 302 CP-Kp bacteraemias, 32 isolates (10.6%) showed MICs of tigecycline ≤ 0.5 mg/L, whereas 177 (58.6%) showed MICs that were 0.75-2 mg/L. Colistin and aminoglycoside susceptibility was observed in 43.0% and 23.8% of isolates, respectively. The majority of isolates carried blaKPC (249; 82.5%), followed by blaVIM (26; 8.6%), both blaKPC and blaVIM (16; 5.3%), and blaNDM (11; 3.6%). Fifteen patients with tigecycline MIC ≤ 0.5 mg/L and 55 with MIC 0.75-2 mg/L were treated with tigecycline monotherapy; 30-day mortality was 20.0% and 50.9%, respectively (p = 0.042). Mortality of 150 patients that received other antimicrobials was 24.7%; among 82 patients that received no appropriate treatment, mortality was 39.0%. No difference in 30-day mortality was observed between patients that received tigecycline (MIC ≤ 0.5 mg/L) or other antimicrobials. Conclusion: Tigecycline monotherapy was as efficacious as other antimicrobials in the treatment of bloodstream infections due to CP-Kp isolates with a tigecycline's MIC ≤ 0.5 mg/L.